A Program for Predicting the Retention Time of Peptides with Post-Translational Modifications - Voronina, A.I.; Rybina, A.V. (Biomedical Chemistry: Research and Methods, 2023)
This paper describes the Retention Time Predictor (RTP) program and web service for predicting the retention time of peptides on a chromatographic column in mass spectrometry experiments. Taking into account post-translational modifications of peptides the program represents a modification of the well-known SSRCalc version 3 (Krokhin, Anal. Chem. 2006, 78(22), 7785-7795). The values of retention coefficients for modified amino acid residues and the algorithm for calculating the isoelectric point value were from the pIPredict program (Skvortsov et al., Biomed. Chem. Res. Meth. 2021, 4(4), e00161). Modifications described in the program include (i) Tandem Mass Tag (TMT) and Isobaric Tags for Relative and Absolute Quantification (iTRAQ) labels; (ii) acetylation, formylation, and methylation of the N-terminal residue and/or lysine side chain; (iii) carbamidomethylation of cysteine, asparagine, and glutamic acid residues; (iv) oxidation and double oxidation of methionine and proline residues; (v) phosphorylation of serine, threonine, and tyrosine residues; (vi) C-terminal amidation of lysine and arginine residues; (vii) formation of propionamide with a cysteine residue. Retention coefficient estimation was based on data from 25 mass spectrometry experiments for which identification was performed from the raw data deposited in the ProteomeXchange database. The RTP program and web service are freely available at http://lpcit.ibmc.msk.ru/RTP.